PENERAPAN MODEL PEMBELAJARAN DIRECT INSTRUCTION (DI) PEMBELAJARAN FISIKA KELAS XI DI SMA NEGERI NIBUNG TAHUN PELAJARAN 2021/2022 - Sri Lestari; Ahmad Amin; Wahyu Arini (Jurnal Perspektif Pendidikan, 2022)
This study aims to determine whether the application of the Direct Instruction learning model can improve the learning outcomes of class XI students in physics lessons at SMA Negeri Nibung. The type of research used is True Experimental Design research. The data collection technique in this study used a test in the form of essay questions on wave material. The design in this study used a design pattern of Pre-test and Post-test one group design because this design did not use a control class. The average value of student learning outcomes in the experimental class is 79.53 and the increase in the average value of student learning outcomes in the experimental class is 56.24. This shows that the physics learning outcomes of class XI students of SMA Negeri Nibung after the implementation of the Direct Instruction model are significantly completed. So it can be concluded that student learning outcomes are significantly completed.